Teses & Dissertações - Ribeiro, Marislei da Silveira; Regal, Paulo Horn; Bortolanza, Felipe; Rausch, Fábio Antônio Flores; Barretto, Ana Isaia; de Mello, Caren Adriana Machado; Habeyche, Candice Campos; Henriques, Sandra Mara Garcia; Christófoli, Eduardo Pires; Ruy, Karine dos Santos; dos Santos, James Machado; Tassi, Stelamaris de Paula Menezes; et al. (Revista FAMECOS, 2011)
.